The Effect of Green Finance and Corporate Social Responsibility on Profitability with Capital Adequacy Ratio as A Moderating Variable - Evi Safitri; Helma Malini; Ana Fitriana; Wendy; Anggraini Syahputri (Journal of Educational Management Research, 2026)
This study aims to analyze the effect of green finance and corporate social responsibility (CSR) on profitability and to examine the moderating role of the capital adequacy ratio (CAR). This research employs a quantitative approach using panel data regression analysis. The data used are secondary data obtained from the annual financial reports of banking companies over a five-year observation period. The sample consists of 16 banking companies with a total of 80 observations. The analytical model applied in this study is the Common Effect Model (CEM). The results show that green finance has a positive and significant effect on profitability, indicating that sustainable financial practices can enhance financial performance. In contrast, CSR does not have a significant effect on profitability. Furthermore, the moderation analysis reveals that CAR strengthens the relationship between green finance and profitability but does not moderate the relationship between CSR and profitability. These findings imply that the implementation of green finance plays an important role in improving banking profitability, particularly when supported by adequate capital strength. This study contributes to the development of the sustainable finance literature and provides insights for financial institutions in formulating strategic financial policies.